Differences between patients' and clinicians' research priorities from the Anaesthesia and Peri‐operative Care Priority Setting Partnership. (31st July 2017) - Boney, O.; Nathanson, M. H.; Grocott, M. P. W.; Metcalf, L.; ,
Summary: The James Lind Alliance Anaesthesia and Peri‐operative Care Priority Setting Partnership was a recent collaborative venture bringing approximately 2000 patients, carers and clinicians together to agree priorities for future research into anaesthesia and critical care. This secondary analysis compares the research priorities of 303 service users, 1068 clinicians and 325 clinicians with experience as service users. All three groups prioritised research to improve patient safety. Service users prioritised research about improving patient experience, whereas clinicians prioritised research about clinical effectiveness. Clinicians who had experience as service users consistently prioritised research more like clinicians than like service users. Individual research questions about patient experience were more popular with patients and carers than with clinicians in all but one case. We conclude that patients, carers and clinicians prioritise research questions differently. All groups prioritise research into patient safety, but service users also favour research into patient experience, whereas clinicians favour research into clinical effectiveness.